Assessment of the safety of priority carcinogenic substances at the level of hygienic regulations in atmospheric air - I.O. Chernychenko; O.M. Lytvychenko; V.F. Babii; O.Ie. Kondratenko; O.P. Rudnytska; D.O. Hlavachek (Medičnì Perspektivi)
The aim of this work was to assess the risk of carcinogenic substances with a proven danger to humans at the level of current maximum permissible concentrations (MPC). The results were obtained on the basis of the collection and analysis of data on chemical carcinogenic compounds that are included in the national regulatory base of permissible content in the atmospheric air of populated areas, as well as the base of Directives of EU countries and the International Agency for the Study of Cancer using bibliosemantic, bibliographic and hygienic research methods. At the same time, the chemical substances classified by experts from International Agency for Research on Cancer in terms of carcinogenicity to humans were taken into consideration: definitely carcinogenic (group 1), probably (group 2A) and possibly carcinogenic to humans (group 2B). As a result, 52 compounds were identified in the list of carcinogenic substances normalized in atmospheric air, of which 12 substances are assigned to group 1, 13 to group 2A, and 27 to group 2B. In this work, only substances of the first group were subject to in-depth analysis. To assess the danger of substances’ concentrations at the level of maximum permissible concentrations, risk indicators according to the recommended methodical documents were determined. Calculations of the carcinogenic risk caused by the concentrations of these substances at the level of hygienic regulations for the atmospheric air of populated areas proved that only for two compounds (benzo/a/pyrene and formaldehyde) the risk is acceptable and meets the international standards recommended by EU and WHO. For other substances of this group, the carcinogenic risk of exposure is excessive. A conclusion was made regarding the need to review the existing hygienic standards from the standpoint of risk and consider them in the future as annual averages. In order to solve this issue, the criterion scale "concentration - carcinogenic risk" was highlighted in the work, with the help of which it was proposed to determine the maximum permissible concentrations according to the indicators of risk acceptable for the conditions of Ukraine.